2003
DOI: 10.1002/hep.1840380415
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Alfa Down–Regulates Collagen Gene Transcription and Suppresses Experimental Hepatic Fibrosis in Mice

Abstract: The equilibrium between the production and degradation of collagen is rigorously controlled by a number of growth factors and cytokines. Interferon alfa (IFN-alpha) is now widely used for the treatment of chronic hepatitis C, which can improve serum levels of fibrotic markers and the degree of hepatic fibrosis, not only in patients who responded to therapy but also in those in whom it is ineffective. These findings may suggest that IFN-alpha possesses direct antifibrotic effects in addition to its antiviral ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(59 citation statements)
references
References 47 publications
2
57
0
Order By: Relevance
“…The antifibrotic potential of HSc025 was further evaluated by histological examination. Consistent with a previous study (19), progressive hepatic fibrosis was induced by repeated CCl 4 injections (Fig. 5E, Control).…”
Section: Hsc025 Treatment Prevents the Progression Of Hepatic Fibrosis-supporting
confidence: 92%
See 1 more Smart Citation
“…The antifibrotic potential of HSc025 was further evaluated by histological examination. Consistent with a previous study (19), progressive hepatic fibrosis was induced by repeated CCl 4 injections (Fig. 5E, Control).…”
Section: Hsc025 Treatment Prevents the Progression Of Hepatic Fibrosis-supporting
confidence: 92%
“…Hepatic fibrosis was induced in C57BL/6 mice by intraperitoneal injections of 0.1 ml/kg body weight of CCl 4 twice a week for 8 weeks as described previously (19). The mice were treated with either 3, 15, and 75 mg/kg/day of HSc025 or vehicle for 4 weeks after injections of carbon tetrachloride for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that IFN significantly suppressed the HSC, and it also inhibited the promoter activity of pro-collagen gene [7] . However, in the clinical practice, fibrosis improvement with IFNbased therapy could be observed only in the virological responders [6] .…”
Section: Discussionmentioning
confidence: 96%
“…However, the histological improvement of liver fibrosis could be observed only in the SVR patients [6] . It has been reported that IFN inhibited the collagen promoter activity in the activated hepatic stellate cells (HSC), which play a pivotal role in liver fibrosis development [7] . Furthermore, it is well…”
Section: Introductionmentioning
confidence: 99%
“…IFN-α and IFN-γ markedly decreases HSC activation and collagen synthesis (177,218) and attenuates ECM deposition in experimental liver fibrosis (219)(220)(221). Studies in patients with chronic hepatitis C suggest that IFN-α may inhibit the progression of liver fibrosis irrespective of virological response (222,223).…”
Section: Hsc As a Target Of Antifibrotic Drugsmentioning
confidence: 99%